Pengaruh Job Description terhadap Kinerja Pegawai pada Kantor Dinas Kependudukan dan Catatan Sipil Kabupaten Sumenep - Dina Kurniawati; Astri Furqani; Moh. Kurdi (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2025)
study aims to analyze the influence of job description on employee performance at the Sumenep Regency Population and Civil Registration Office. The background of this research is based on the importance of clarity of job descriptions in supporting the optimal performance of employees, especially in public service agencies that deal directly with the community. This study uses a quantitative approach with the Partial Least Square (PLS) data analysis technique through the help of Smart PLS 2.0 M3 software. Primary data was obtained through the distribution of questionnaires to 20 respondents who were selected using the purposive sampling technique. The results showed that job description had a positive and significant effect on employee performance, with a path coefficient value of 0.808 and an R-square value of 0.652. This shows that the clearer the job description received by employees, the higher the level of performance produced. Job descriptions play an important role in improving work efficiency, minimizing role conflicts, clarifying responsibilities, and supporting an objective performance evaluation process. This study suggests that government agencies regularly update and socialize job descriptions to all employees to improve the performance of individuals and organizations as a whole.